2020
DOI: 10.3390/s20236770
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Walking Distance in Persons with a Lower Limb Amputation

Abstract: The distance one can walk at a time could be considered an important functional outcome in people with a lower limb amputation. In clinical practice, walking distance in daily life is based on self-report (SIGAM mobility grade (Special Interest Group in Amputee Medicine)), which is known to overestimate physical activity. The aim of this study was to assess the number of consecutive steps and walking bouts in persons with a lower limb amputation, using an accelerometer sensor. The number of consecutive steps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The presented sensor-based method may provide a useful approach for early detecting and tailoring the treatment of circadian disruptions in rehabilitation populations. Hofstad et al (2020) [15] measured the number of consecutive steps and walking bouts in persons with a lower limb amputation using three accelerometers: one in each trouser pocket and one on the sternum. Measurements were performed for two consecutive days in 20 persons with a lower limb amputation and 10 age-matched controls.…”
Section: Labarierre Et Al (2020)mentioning
confidence: 99%
See 1 more Smart Citation
“…The presented sensor-based method may provide a useful approach for early detecting and tailoring the treatment of circadian disruptions in rehabilitation populations. Hofstad et al (2020) [15] measured the number of consecutive steps and walking bouts in persons with a lower limb amputation using three accelerometers: one in each trouser pocket and one on the sternum. Measurements were performed for two consecutive days in 20 persons with a lower limb amputation and 10 age-matched controls.…”
Section: Labarierre Et Al (2020)mentioning
confidence: 99%
“…Hofstad et al (2020) [ 15 ] measured the number of consecutive steps and walking bouts in persons with a lower limb amputation using three accelerometers: one in each trouser pocket and one on the sternum. Measurements were performed for two consecutive days in 20 persons with a lower limb amputation and 10 age-matched controls.…”
mentioning
confidence: 99%
“…Six studies added a Global Positioning System (GPS) device in addition to the activity monitors [ 54 , 103 , 105 , 110 , 114 ]. Other wearable technologies used in the included studies were TEMEC activity monitor (Temec Technologies BV, Heerlen, The Netherlands) [ 63 , 67 ], Dynaport ADL (McRoberts BV, The Hague, The Netherlands) [ 62 , 119 ], Power Walker (Yamax Health & Sports Inc., Shropshire, UK) [ 85 ], EmpowerGO (Hanger Inc., Austin, TX, USA) [ 24 ], Up move (Jawbone, San Francisco, CA, USA) [ 35 ], Activ 8 (VitaMove, Veldhoven, The Netherlands) [ 38 ], Uptimer (National Ageing Research Institute, Victoria, Australia) [ 66 ], AMP 331 (Dynastream Innovations, Cochrane, AB, Canada) [ 97 ], and the MiniMods Dynaport (McRoberts BV, The Hague, The Netherlands) [ 33 ]. Two studies used an accelerometer, but did not specify the manufacturer [ 55 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The articles were structured into four categories, based on the primary reason for using wearable technology: observational studies ( n = 46), interventional studies ( n = 34), algorithm/method development studies ( n = 12), and validity/feasibility studies ( n = 6). Of the 46 included observational studies, 13 studies aimed to describe characteristics of real-world behavior [ 21 , 26 , 33 , 40 , 60 , 63 , 66 ], real-world measurements in a specific population [ 44 , 50 , 62 ], or at a specific moment in time, such as post-rehabilitation [ 21 , 45 , 50 ], or during a mountaineering expedition [ 59 ]. Four studies observed changes in real-world behavior over time, including changes between before and during the COVID-19 pandemic [ 24 , 27 ], during in-patient and leave periods [ 36 ], and before and after prosthetic disuse [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation